Hypersensitivity Among Special Education Class Students (Journal of the College of Basic Education, 2025)
The current research aims to identify the impact of hypersensitivity on the psychological and social adjustment of special education students at Al-Rand and Al-Sahel Al-Akhdar Schools. The researcher relied on the descriptive correlational approach, and the study sample consisted of (40) male and female students.What are the statistical methods?Pearson's correlation coefficientT-test for one sampleT-test for two controlled samplesWhat is the methodology?The researcher used the descriptive analysis approach.What are the results of the research?Hypersensitivity among below-average special education students